ҚОРАҚАЛПОҚ ХАЛҚ ДОСТОНИ «ШАҲРИЁР» – ЎРТА АСРЛАРДАГИ УЙҒОНИШ ДАВРИНИНГ БЕБАҲО ПЕДАГОГИК МЕРОСИ - Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2022)
The article provides a comprehensive scientific and theoretical analysis of the period of creation of the Karakalpak folk epic "Shahriyor". It is also given the educational perspectives, and on the basis of these concepts it is concluded that the epic is one of the invaluable pedagogical heritage of the early Renaissance.
Keywords: "Shahriyor" epic; I and II Renaissance period; views on the divinity and Islam in the epic; educational views on the pedagogy of the Awakening period in the epic